Crop reproductive meristems in the genomic era: a brief overview. (23rd June 2020) - Caselli, Francesca; Zanarello, Fabio; Kater, Martin M.; Battaglia, Raffaella; Gregis, Veronica
Abstract : Modulation of traits beneficial for cultivation and yield is one of the main goals of crop improvement. One of the targets for enhancing productivity is changing the architecture of inflorescences since in many species it determines fruit and seed yield. Inflorescence shape and organization is genetically established during the early stages of reproductive development and depends on the number, arrangement, activities, and duration of meristems during the reproductive phase of the plant life cycle. Despite the variety of inflorescence architectures observable in nature, many key aspects of inflorescence development are conserved among different species. For instance, the genetic network in charge of specifying the identity of the different reproductive meristems, which can be indeterminate or determinate, seems to be similar among distantly related species. The availability of a large number of published transcriptomic datasets for plants with different inflorescence architectures, allowed us to identify transcription factor gene families that are differentially expressed in determinate and indeterminate reproductive meristems. The data that we review here for Arabidopsis, rice, barley, wheat, and maize, particularly deepens our knowledge of their involvement in meristem identity specification.